Characteristics of analytically confirmed gamma-hydroxybutyrate (GHB) positive patients in the emergency department: presentation, poly-drug use, disposition and impact on intensive care resource utilisation. (3rd April 2023) - Stockham, Peter; Partridge, Emma; Alfred, Sam; Boyle, Laura; Camilleri, Andrew; Green, Hannah; Haustead, Daniel; Humphries, Melissa; Kostakis, Chris; Mallon, Jake
Abstract: Background: Gamma-hydroxybutyrate is a potent central nervous system depressant with a narrow recreational dose window and analytical detection time. We describe data relating to intoxicated patients presenting to emergency departments across metropolitan Adelaide who tested positive for gamma-hydroxybutyrate. This work was part of the Emergency Department Admission Blood Psychoactive Testing study. Methods: Over a 15-month period, patients presenting to four metropolitan emergency departments with symptoms of drug intoxication were enrolled in the study. The methodology involved the collection of demographic and clinical data and a de-identified blood sample which underwent comprehensive toxicological analysis. Gamma-hydroxybutyrate was determined using an acid-catalysed cyclisation followed by liquid-liquid extraction and gas chromatography-mass spectrometry. Data relating to samples positive for gamma-hydroxybutyrate were examined. Results and discussion: A total of 1120 patients were enrolled between March 2019 and May 2020, 309 of whom were positive for gamma-hydroxybutyrate (27.6%). Of these, 256 (83%) were also positive for metamfetamine (methamphetamine). The most common clinical observation in gamma-hydroxybutyrate-positive patients was central nervous system depression (89%). There was a significant relationship between gamma-hydroxybutyrate status and sex; although males outnumbered females in absolute terms, a higher proportion of females (32%) tested positive for gamma-hydroxybutyrate than males (25%, P  = 0.0155). Blood gamma-hydroxybutyrate concentrations ranged from 10 to 651 mg/L (0.096–6.2 mmol/L) and increasing gamma-hydroxybutyrate concentration correlated with severe toxicity. The presence of gamma-hydroxybutyrate had a significant impact on the patient discharge destination: the majority (69.2%) of gamma-hydroxybutyrate-positive patients were managed and discharged from the emergency department or their attached short stay wards. A significantly higher proportion of gamma-hydroxybutyrate-positive patients were admitted to the intensive care unit (28.2%) compared with gamma-hydroxybutyrate-negative patients (12.7%, chi-squared = 36.85, P  <0 .001). Gamma-hydroxybutyrate positive cases accounted for 45.8% of all study-related intensive care unit admissions. Conclusions: Gamma-hydroxybutyrate is commonly detected in illicit drug-related emergency department presentations and is detected disproportionately in the patient cohort who require intensive care unit level care.